Integrasi Pendidikan Agama Islam dan Budaya Lokal Sebagai pendekatan strategis dalm meningkatkan relevansi dan efektivitas pendidikan agama - Walina Syifa (Integrated Education Journal, 2024)
The integration of Islamic Religious Education (PAI) and local culture is a strategic approach to enhancing the relevance and effectiveness of religious education in communities rich in local traditions. The aim of this study is to improve the integration of Islamic religious education and local culture, and to explore how combining Islamic values with local wisdom can enrich the learning process, strengthen cultural identity, and foster social harmony. In examining the integration of Islam and local culture, the author employs a qualitative research method by collecting data through library research. The findings of this study indicate that integrating Islamic Religious Education and local culture can deepen learners' understanding of religion in a more contextual way that aligns with local values, while also promoting the preservation of traditional culture. Emphasizing the universal values of Islam that are in synergy with local wisdom can also strengthen mutual respect and tolerance among community members. The conclusion of this study is that effective integration requires collaboration among educators, religious leaders, and the community to design a harmonious curriculum, along with training that supports consistent implementation in practice. This approach not only enriches religious education but also contributes to a more inclusive and dynamic cultural diversity